2020
DOI: 10.1158/0008-5472.can-19-3184
|View full text |Cite
|
Sign up to set email alerts
|

Consumption of the Fish Oil High-Fat Diet Uncouples Obesity and Mammary Tumor Growth through Induction of Reactive Oxygen Species in Protumor Macrophages

Abstract: Obesity is associated with increased risk of many types of cancer and can be induced by various high-fat diets (HFD) from different fat sources. It remains unknown whether fatty acid composition in different HFD influences obesity-associated tumor development. Here we report that consumption of either a cocoa butter or fish oil HFD induced similar obesity in mouse models. While obesity induced by the cocoa butter HFD was associated with accelerated mammary tumor growth, consumption of the fish oil HFD uncouple… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
59
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(70 citation statements)
references
References 45 publications
1
59
0
Order By: Relevance
“…However, this phenomenon is non-universal and is largely related to the FA subtype. For example, fish oil-fed mice possess a lower percentage of pro-tumor macrophages and interleukin (IL-10) expression and higher infiltrations of B cells and CD + 8 T cells than coco butter-fed mice [ 67 ]. In addition, the enrichment of polyunsaturated fatty acids (PUSFAs), not saturated fatty acids (SFAs), exerts higher cytotoxicity on macrophages against tumor cells [ 68 ].…”
Section: Anti-tumor Effects Of Lipids In Tumor Immune Responsementioning
confidence: 99%
“…However, this phenomenon is non-universal and is largely related to the FA subtype. For example, fish oil-fed mice possess a lower percentage of pro-tumor macrophages and interleukin (IL-10) expression and higher infiltrations of B cells and CD + 8 T cells than coco butter-fed mice [ 67 ]. In addition, the enrichment of polyunsaturated fatty acids (PUSFAs), not saturated fatty acids (SFAs), exerts higher cytotoxicity on macrophages against tumor cells [ 68 ].…”
Section: Anti-tumor Effects Of Lipids In Tumor Immune Responsementioning
confidence: 99%
“…In another in vitro study using a different murine macrophage cell line, J774, a large increase in the intracellular ROS was observed by incubation with DHA, EPA, oleic acid, linoleic acid and arachidonic acid at 100 μM for 1 h 59 , while no cytotoxicity was recorded. Furthermore, the fish oil-derived polyunsaturated n-3 fatty acids (e.g., EPA, DPA) were found to induce the death of mice bone marrow-derived macrophages at 200 μM through promoting intracellular ROS products as early as 30 mins after treatment 60 Another important conclusion we are proposing here is that CAT-triggered superoxide eruption in FONE can cause macrophage cell death through ferroptosis and autophagy, but not apoptosis. The cell death was effectively prohibited by using the ferroptosis inhibitor liproxstatin-1, which acts as a potent radical-trapping antioxidant 33 to scavenge the superoxide anions.…”
Section: Discussionmentioning
confidence: 58%
“…In another in vitro study using a different murine macrophage cell line, J774, a large increase in the intracellular ROS was observed by incubation with DHA, EPA, oleic acid, linoleic acid and arachidonic acid at 100 μM for 1 h 59 , while no cytotoxicity was recorded. Furthermore, the fish oil-derived polyunsaturated n -3 fatty acids (e.g., EPA, DPA) were found to induce the death of mice bone marrow-derived macrophages at 200 μM through promoting intracellular ROS products as early as 30 mins after treatment 60 . In general, EPA boosts cellular ROS, despite the different origin of the macrophage cells or different treatment times.…”
Section: Discussionmentioning
confidence: 99%
“…E-FABP (FABP5) has a stronger affinity for n-3 PUFAs than the others [113]. Moreover, adipose/macrophage FABP (A-FABP, FABP4) mediates ROS-mediated pro-tumor macrophage death induced by n-3 PUFAs [114].…”
Section: Pufas and Their Roles In Carcinogenesismentioning
confidence: 99%
“…However, it has decreased the number of pro-tumorigenic macrophages. This phenomenon was an effect of the significant ROS generation and subsequent TAM's apoptosis in the mechanism derived by adipose/macrophage-fatty acid-binding protein [114]. In the study of Liang et al, it was shown that in the case of the mice allografted with cancer androgen-sensitive prostate cancer cells fed with a high-fat diet (HFD) rich in n-3 FA TAMs proinflammatory cytokines (IL-6, TNF alpha and IL-10) and the chemoattractant protein (CCL-2) were lower expressed when compared to the animals fed an HFD based on n-6 FA [143].…”
Section: Effects Of N-3 Pufa On Tumor-associated Macrophages and Cancermentioning
confidence: 99%